2021
DOI: 10.3390/app11104619
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Geotrichum candidum Growth in Milk

Abstract: The study of microbial growth in relation to food environments provides essential knowledge for food quality control. With respect to its significance in the dairy industry, the growth of Geotrichum candidum isolate J in milk without and with 1% NaCl was investigated under isothermal conditions ranging from 6 to 37 °C. The mechanistic model by Baranyi and Roberts was used to fit the fungal counts over time and to estimate the growth parameters of the isolate. The effect of temperature on the growth of G. candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…On smear ripened cheeses, these yeasts have been reported to provide growth factors for the smear bacteria (Beresford et al, 2001;Cogan, 2016). However, uncontrolled yeast growth is not beneficial as this can lead to off-flavors, slick rinds, and toad skin deformities (Westall & Filtenborg, 1998;Šipošová, Koňuchová, Valík, Trebichavská, & Medved'ová, 2021). Here, we have demonstrated that the anti-yeast effect of B. linens CX3, at least partially, can be attributed to its ammonia production.…”
Section: Ammonia and High Ph Effectively Kill Yeastmentioning
confidence: 74%
“…On smear ripened cheeses, these yeasts have been reported to provide growth factors for the smear bacteria (Beresford et al, 2001;Cogan, 2016). However, uncontrolled yeast growth is not beneficial as this can lead to off-flavors, slick rinds, and toad skin deformities (Westall & Filtenborg, 1998;Šipošová, Koňuchová, Valík, Trebichavská, & Medved'ová, 2021). Here, we have demonstrated that the anti-yeast effect of B. linens CX3, at least partially, can be attributed to its ammonia production.…”
Section: Ammonia and High Ph Effectively Kill Yeastmentioning
confidence: 74%
“…The occurrence of Acinetobacter johnsonii , Staphylococcus spp., and Candida parapsilosis has previously been documented in raw milk of the same sheep breed [ 34 , 35 ]. Geotrichum species, mainly G. candidum , are also commonly associated with milk and cheese [ 57 , 58 , 59 ]; although recognized as synonym of Galactomyces candidus [ 60 ] due to phylogenetic affinity, to the best of the authors’ knowledge this is the first study reporting the identification of Geotrichum silvicola in raw ewe’s milk and cheese. Great interest is addressed to the yeast Yarrowia lipolytica for its proteolytic and lipolytic activities, and the consequent aroma development during cheese ripening [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deamination reactions performed by G. candidum , which lead to the production of aldehydes, ammonia, and organic acids, influence the cheese’s sensorial characteristics [ 3 , 37 , 38 ]. In general, G. candidum -associated sensorial characteristics include mildly cheesy, sweaty, moldy, yeasty, fermented, acidic, putrid, cidery, musty, and fruity flavors, and lightly velvety or fluffy appearance [ 3 , 39 ].…”
Section: Administration As a Starter Culturementioning
confidence: 99%